Nomenclature and taxonomic notes on the controversial species Cacalia senecioides (Compositae) - Calvo, Joel (Phytotaxa, 2016)
The taxonomic interpretations of Cacalia senecioides Kunth in Humboldt et al. (1818: 129) changed over time and depending on the authors because the original material is not well preserved and not enough taxonomically informative. In the mid-19th century, Weddell (1856) already noticed: “Les échantillons qui représentent cette espèce dans l’herbier de Humboldt et Bonpland sont en mauvais état; mais leur examen a suffi pour me convaincre que la description de Kunth est très défectueuse” [Humboldt & Bonpland’s specimens of C. senecioides are in bad condition; but after studying them I am convinced that Kunth’s description is very imperfect]. Certainly, Kunth’s description does not allow to unequivocally identify this species and the description of the indumentum of the leaves is inaccurate. Nevertheless, he pertinently described the leaves as “reticulate-venosa”. In my opinion the reticulate leaves is a useful character to discriminate C. senecioides from other species that might fit in the description, at least on dry specimens.